The Mandatory Convertible Bond Is An Instrument to Pursue Dominant Position Among Shareholders - Go Chin Tjwan; Ferdian Handoyo Ang; Anthony Lianto (Melayunesia Law, 2025)
This study examines the strategic and legal implications of Mandatory Convertible Bonds (MCBs) as hybrid financial instruments that combine the characteristics of debt and equity. MCBs are distinct in that they mandatorily convert into equity at maturity, offering issuers both a mechanism to reduce leverage and a strategic tool to influence ownership structures. In the context of corporate finance, these instruments serve as a bridge between fixed-income security and potential equity participation, providing issuers with lower financing costs while granting investors the opportunity for capital appreciation. Previous studies, such as those by Chemmanur (2006) and Pajak (2008) have predominantly explored the financial efficiency, valuation models, and agency problems related to MCBs. However, limited attention has been given to their legal implications, particularly concerning their potential use in pursuing dominant control among shareholders. This paper adopts a normative juridical research method utilizing statute, conceptual, and comparative approaches to examine how MCBs are regulated and applied in Indonesia, the European Union, and the United States. The findings indicate that mandatory conversion mechanisms allow issuers to strategically dilute existing shareholders and reallocate voting power to selected investors, thereby strengthening corporate control. Such practices demonstrate the dual nature of MCBs—not only as financial innovation but also as instruments with potential implications for corporate governance and fairness among shareholders. The study concludes that to ensure equitable stakeholder protection, the issuance of MCBs requires clear regulatory safeguards and adherence to evolving international standards.